A hydrothermally stable ytterbium metal–organic framework as a bifunctional solid-acid catalyst for glucose conversion. Issue 76 (5th September 2019) - Burnett, David L.; Oozeerally, Ryan; Pertiwi, Ralentri; Chamberlain, Thomas W.; Cherkasov, Nikolay; Clarkson, Guy J.; Krisnandi, Yuni K.; Degirmenci, Volkan; Walton, Richard I.
Abstract : A ytterbium–organic framework containing Lewis and Brønsted acid sites that effects transformation of glucose to 5-HMF in water at 140 °C. Abstract : Yb6 (BDC)7 (OH)4 (H2 O)4 contains both bridging hydroxyls and metal-coordinated waters, possessing Brønsted and Lewis acid sites. The material crystallises from water at 200 °C. Using the solid as a heterogenous catalyst, glucose is converted into 5-hydroxymethylfurfural, via fructose, with a total selectivity of ∼70% after 24 hours at 140 °C in water alone: the material is recyclable with no loss of crystallinity.